COMPARISON OF PREVIOUSLY ESTABLISHED RISK FACTORS IN PREDICTING PTSD SYMPTOM SEVERITY IN THE FIRST SIX MONTHS POST-TRAUMA - (:unkn) unknown (My University, 2024)
This study aims to improve our understanding of the predictive value of previously identified risk factors for the severity of Post-Traumatic Stress Disorder (PTSD) symptoms after a traumatic event. We recruited 178 participants from an Emergency Department and assessed four constructs previously associated with PTSD in the first few weeks after trauma and their relationship to PTSD symptom severity at six-month follow-up. Using structural equation modeling we examined four latent variables as predictors of PTSD symptom severity, cognitive attributions, trauma history, emotion response and regulation, and socioeconomic factors, along with two mediators, sleep quality and self-perceived pain. Our findings indicate that cognitive attributions soon after trauma and a history of trauma are closely linked to the severity of PTSD symptoms six months later. Sleep quality and self-perceived pain partially mediated the relationship between cognitive attributions and PTSD symptom severity, highlighting their significant roles in the progression of PTSD. The study also revealed that emotion responding and regulation, measured shortly after trauma, indirectly influenced PTSD symptom severity at six months through their impact on sleep quality, underscoring the critical role of emotional processes in the trajectory of PTSD development. In addition to providing valuable insights into the mechanisms driving PTSD symptomatology, this research also provides important insights into the development of targeted interventions aimed at mitigating the long-term psychological effects of trauma. Key words: Post-Traumatic Stress Disorder (PTSD), structural equation modeling, cognitive attributions, trauma history, emotion response and regulation, socioeconomic factors, sleep, pain
Keywords: cognitive attributions; emotion response and regulation; Post-Traumatic Stress Disorder (PTSD); socioeconomic factors; structural equation modeling (SEM); trauma history